The social approach in Mahmoud Darwish's Poem "To My Mother": An analysis of the symbolism of identity and nostalgia - Adwan, Rakan Abu Arabi; Almazaidah, Ismail Suliman; AlTalafeeh, Asma Sayel (Research Journal in Advanced Humanities, 2025)
This research aims to explore the relationship between the social approach and prison literature, with a focus on Mahmoud Darwish's experience as a poet of the Palestinian cause. The study seeks to understand how Darwish's texts reflect the social and political contexts that influenced them, emphasizing the symbolism of his poem "To My Mother" as a representation of identity, nostalgia, and connection to the homeland.The research adopts the social approach in literary analysis, interpreting texts as reflections of social and political realities. This approach is employed to study Darwish's works within the contexts of the Palestinian Nakba, exile, and diaspora. The analysis also incorporates prison literature to understand the feelings of alienation and oppression evident in his works. The study revealed that the social approach highlights Darwish's ability to intertwine the individual and collective suffering of the Palestinian people. The poem "To My Mother" showcases the symbolism of the mother as a personification of the homeland and a longing for roots in the face of exile and alienation. The study also demonstrated that prison literature and Darwish's works share common themes of oppression and deprivation while emphasizing hope for liberation and return. The findings confirm that the social approach is an effective tool for understanding Mahmoud Darwish's works, as it helps uncover the connections between literary texts and social and political issues. Darwish's literature authentically represents the Palestinian experience in the diaspora, enriched by its ability to convey the suffering of his people to the world through profound symbolism and a deeply human style.